Psychological Distress and Its Mediating Effect on Experiences of Online Risk: The Case for Vulnerable Young People - El-Asam, Aiman; Lane, Rebecca; Katz, Adrienne (Frontiers in Education, 2022)
Recent research concludes that vulnerable children and adolescents are disadvantaged socially, psychologically, and online. This study aimed to examine participants’ vulnerability (vulnerable vs. non-vulnerable), psychological distress, parental e-safety support, and online lives, specifically their experiences of online risk. The roles of psychological distress and parental e-safety support were explored as possible mediators and moderators, respectively, for the relationship between vulnerability and online risk. Survey data was collected from 15,278 participants (11-17 years old; M = 12.60, SD = 1.44), 46.6% identified as females, 46.6% identified as males and 6% identified as “other”. Participants were recruited from schools/colleges in different parts of England, of whom 3,242 were categorised as vulnerable. Using appropriate statistical tests, the results showed that, when compared to the non-vulnerable participants, the vulnerable groups (single or multiple vulnerabilities) experienced more psychological distress and online risks. They also received less e-safety support from parents or carers. Furthermore, the relationship between vulnerability and online risk was significantly and partially mediated by psychological distress. Parental e-safety support was found to moderate the relationship between psychological distress and online risk and between vulnerability and online risk. In conclusion, the results demonstrated that vulnerability offline is mirrored online. Psychological interventions and parental e-safety support are required to navigate the internet safely. Children’s services and practitioners ought to consider online risks in their assessments and interventions.